Will Countries that Receive Insufficient Aid Please Stand Up? - Utz, Robert (World Bank, Washington, DC, 2017)
The Accra Agenda for Action contains a commitment to increase aid effectiveness by 'addressing the issue of countries with insufficient aid.' This paper highlights the difficulties in identifying such countries unequivocally, given the limited theoretical and empirical knowledge on optimal aid allocations. Actual aid receipts by low income countries are compared to several benchmarks derived from different aid allocation models. These models differ primarily with regard to the weights assigned to country needs and performance. The analysis shows that different aid allocation models identify different sets of countries as receiving insufficient aid. The paper does not find a greater tendency for fragile states to receive insufficient aid compared to non-fragile states. However, there appears a greater tendency for bilateral aid to leave countries with insufficient aid compared to multi-lateral aid, which in fact in many cases partly compensates for under-funding from bilateral donors. The potential aggregate cost of increasing aid to countries with insufficient aid varies significantly depending on which aid allocation model is used, but could be as high as US$ 7 billion annually. Enhanced coordination of donors' aid allocation decisions to ensure that no low income country ends up inadvertently as an aid orphan will be an important step in addressing 'the issue of countries with insufficient aid.'